Tuberculosis is still a cause of infertility in developing countries (Journal of Institute of Medicine Nepal, 2011)
Introduction: Infertility is global problem. Tuberculosis salpingitis is a very rare condition in developed countries but in developing part of the world it is still a problem. One of the commonest symptoms of pelvic tuberculosis is primary infertility. Though infrequent, pelvic tuberculosis is still a cause of infertility in Nepal. Methods: This is a prospective descriptive study conducted in the ‘Infertility clinic’, Department of Obstetrics and Gynaecology, Tribhuwan University, Teaching hospital, Kathmandu in 2423 patients from April2005-March2009. All couples were investigated with simple non invasive tests like total blood count with erythrocyte sedimentation rate (ESR), mantoux test, Adenosine diaminase (ADA), polymerase chain reaction (PCR), to invasive procedure like endometrial biopsy to rule out tuberculosis. Result: Of the total of 2423 infertility among the 37 cases were found to have pelvic tuberculosis contributing to infertility. Of them, 19 patients of them were investigated in private centers for infertility and none of them had investigations for tuberculosis. Out of these 19 cases 5 women were treated in the line of tubal block by hydrotubation without performing investigations for tuberculosis. All of these 37 patients had suspicion of tuberculosis either in the history or investigation. After treatment six patients conceived but only two had successful pregnancy. Conclusions: Pelvic tuberculosis is still a problem in Nepal affecting the fertility and hence should be considered in the management.. Key words; pelvic tuberculosis; female infertility; tuberculosis; endometritis DOI: http://dx.doi.org/10.3126/joim.v32i2.4943 Journal of Institute of Medicine, August, 2010; 32: 33-35